ANALISIS EFISIENSI BUDIDAYA IKAN LELE DAN IKAN PATIN DI KECAMATAN WAY PANJI KABUPATEN LAMPUNG SELATAN - Ubay, Meita Saniyyah; Prasmatiwi, Fembriarti Erry; Haryono, Dwi (Universitas Galuh, 2023)
This study aims to measure the technical and economic efficiency of catfish and pangasius farming in Way Panji, South Lampung. The number of research samples was 40 catfish farmers and 44 pangasius farmers. The research was held in March-April 2022. The analysis used to calculate fish farming efficiency used stochastic frontier production function analysis. The results showed that the level of technical efficiency in catfish and pangasius farming in Way Panji has reached efficiency with an average of 0.85 and 0.82. The level of economic efficiency in catfish farming has not been efficient with an average of 0.66; While the level of economic efficiency in pangasius farming is very efficient with an average of 0.99.